Performance appraisals & phrases - Lloyd, Kenneth L. (--For dummies., 2025)
The newest steps and strategies to enhance the performance appraisals you provide Performance Appraisals & Phrases For Dummies shows you how to apply the latest performance appraisal practices and generate positive outcomes for your employees, for your company, and for you. The days of stand-alone annual performance appraisals are drawing to a close, with today's appraisals utilizing quarterly or biannual sessions, continuous feedback with regular two-way communication, collaborative goal-setting, career development, and an ongoing forward focus. This approach includes tools to provide impactful feedback and feedforward, recognize and support employee success, avoid the common mistakes related to performance appraisals, and build your coaching skills. Gain a clear understanding of the ways that performance appraisals contribute to individual and organizational success. Provide productive feedback by accessing more than 3,300 phrases. Lead appraisal sessions that resonate with your employees and set the stage for improved performance and career development. By applying the newest steps in performance appraisals, you will literally and figuratively be in an excellent position to build your employees' skills, motivation, performance, satisfaction, and commitment.